2015
DOI: 10.1063/1.4939119
|View full text |Cite
|
Sign up to set email alerts
|

Strong magnetic fields generated with a simple open-ended coil irradiated by high power laser pulses

Abstract: A new simple mechanism due to cold electron flow to produce strong magnetic field is proposed. A 600-T strong magnetic field is generated in the free space at the laser intensity of 5.7 × 10 15 ⋅ −2 . Theoretical analysis indicates that the magnetic field strength is proportional to laser intensity. Such a strong magnetic field offers a new experimental test bed to study laser-plasma physics, in particular, fast-ignition laser fusion research and laboratory astrophysics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Using nondestructive magnets, fields on ∼ 1 MG a) Electronic mail: shi9@llnl.gov level are routinely generated at user facilities worldwide [10][11][12][13] . Moreover, with destructive magnets, much higher fields have been obtained using laser-driven targets [14][15][16][17][18] and magnetic flux compression [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Using nondestructive magnets, fields on ∼ 1 MG a) Electronic mail: shi9@llnl.gov level are routinely generated at user facilities worldwide [10][11][12][13] . Moreover, with destructive magnets, much higher fields have been obtained using laser-driven targets [14][15][16][17][18] and magnetic flux compression [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Another technique is to use a laser-driven capacitor–coil target 22 to generate a strong magnetic field. The strength of the magnetic field was measured on GEKKO-XII 23 , 24 , LULI2000 25 , Shengguang-II 26 , and OMEGA-EP laser facilities 27 , 28 . As discussed in the Supplementary Discussion and summarized in Supplementary Table 1 , experimental results revealed that a 600–700-T magnetic field was generated by using a tightly focused kilo-joule and nano-second infrared ( λ L = 1.053 μm) laser beam.…”
Section: Introductionmentioning
confidence: 99%
“…Strong magnetic field of hundreds of Teslas or several MG was demonstrated on the experimental platform of ShenGuang(SG)-II laser facility by irradiating 2 kJ in 1 ns on a planar plate attached on the end of one open-ended coil [23]. The magnetic field is generated by cold background electrons to neutralize the positively charged laser foci, which has a different physical mechanism from the previous study of magnetic fields driven by hot electron current in a capacitorcoil target [24].…”
Section: Controllable Way For Generating Magnetic Field Larger Than 1mentioning
confidence: 99%